Inovasi Strategi Pembelajaran PAI dalam Meningkatkan Karakter Religius Siswa di SMA Negeri 7 Purworejo - Lestari, Prawidya; ‘Izzah, Dinal (QUALITY, 2021)
The purpose of this study was to find out the background of the character education strengthening program in schools, policies for strengthening and developing character education in schools and forms of innovation in PAI learning strategies to improve the religious character of students at SMAN 7 Purworejo.  This type of research is qualitative. Methods of data collection using interviews, observation and documentation. This study resulted in several statements, namely: (1) The background of the character strengthening program in schools is that schools are one of the important environments in character education and moral degradation occurs (2) the policy of the school's character education program is stated in the vision and mission of the institution and strengthened by the Decree of the Head of School. School about the school's PPK Team. (3) Innovative forms of PAI learning strategies by implementing the development and strengthening of class-based character education, school culture-based and community-based. Assessment of the achievement of character education is carried out by direct observation and monitoring and the use of student activity journals.